Magnetic, recyclable PtyCo1−y/Ti3C2X2 (X = O, F) catalyst: a facile synthesis and enhanced catalytic activity for hydrogen generation from the hydrolysis of ammonia borane. (14th March 2017) - Fan, Guangyin; Li, Xiaojing; Ma, Yuling; Zhang, Yun; Wu, Jiangtao; Xu, Bin; Sun, Ting; Gao, Daojiang; Bi, Jian
Abstract : Magnetic recyclable Pt y Co1− y /Ti3 C2 X2 (X = O, F) catalyst exhibits excellent catalytic performance for the hydrolysis of AB at room temperature. Abstract : Exploring the applications of two dimensional layered Ti3 C2 X2 (X = OH, F) is of great importance because of its excellent physical and chemical properties. Herein, we report the synthesis of the bimetallic catalyst Pt y Co1− y /Ti3 C2 X2 via a facile one-pot approach using Ti3 C2 X2 as the support. The in situ synthesized Pt y Co1− y /Ti3 C2 X2 is subsequently applied as a catalyst for hydrogen evolution from the hydrolysis of ammonia borane at 25 °C. Experimental results show that Pt0.08 Co0.92 /Ti3 C2 X2 exhibits excellent catalytic activity for the hydrolysis of ammonia borane with a high hydrogen generation rate of 100.7 L H2 (min gPt ) −1 and turnover frequency of 727 mol H2 (min molPt ) −1 because of the synergistic effect between Pt and Co. Moreover, Pt0.08 Co0.92 /Ti3 C2 X2 could be recovered from the reaction mixture by a magnet and recycled at least seven times, thus showing its high recycling efficiency.